Implementasi Aplikasi Business Intelligence Untuk Memonitor Efisiensi Pengelolaan Rumah Sakit - Herwanto Herwanto; Ali Khumaidi (STMIK Budi Darma, 2020)
The need for fast and accurate information has become the need of every company, including hospitals. This is one of the factors that makes a company superior to other companies. In making the right and accurate decisions, leaders need information that is presented clearly, easily understood, on time, and in accordance with needs. To support the presentation of such information a database, data warehouse and other applications that are easy to understand are needed. Hospitals as a socio-economic institution are not only required to provide solutions to health problems but are also demanded to always improve the quality of their services. For this purpose to be achieved, its management must be efficient. Service indicators can be used as a measuring tool to assess the level of management efficiency. Business Intelligence (BI) application is one form of implementation that is able to facilitate management to monitor hospital performance. This research explores the use of information technology to build BI applications, reviewing the right approach in building BI applications, as well as several important aspects that must be considered for the system work for the hospital environment. There are two main stages in building this application, namely: building a data warehouse originating from an electronic medical record database and hospital operations, and building a BI application. With the formation of this BI application, it is very useful for hospital management in managing their institutions better